Problematika dan Pengendalian Terminal Bayangan di Indonesia - Ramadhan Dwi Prasetyo; Reza Yoga Anindita (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2024)
This research provides insight into the complexity of the shadow terminal phenomenon and how improvements in the public transportation system can provide better solutions to the mobility needs of people in Indonesia. The mix method approach is a qualitative and quantitative method used in this research by conducting in-depth interviews with 15 informants consisting of employees of the Land Transportation Management Center, Transportation Service, Type A official terminal, Police and Land Transport Organization. Second, by distributing 150 questionnaires to shadow terminal users, as well as field observations in affected locations. The research results reveal that several key factors that influence passengers' decisions in using shadow terminals are cost, time and accessibility. People feel compelled to choose shadow terminals because of lower costs, and better speeds, as well as marriage in schedules. The time factor and lack of facilities at the official terminal also trigger passengers to look for alternative transportation. The implication of the phenomenon of the spread of shadow terminals is that there are challenges in maintaining the quality and movement of official public transportation services. Therefore, a holistic solution is needed to improve service quality and meet passenger needs. Some of the recommendations resulting from this research include improving official terminal facilities, improving punctuality, adjusting tariffs to be more affordable, educational campaigns, developing official applications, and collaboration between stakeholders. By overcoming the challenges that arise from this phenomenon, it is hoped that official public transportation services can become more effective and better meet passenger needs.